Bahan Ajar Fisika Berbasis Majalah Terintegrasi I-SETS (Islamic, Science, Environment, Technology, Society) dan Muatan Karakter - Popilayah, Padilah; Astuti, Budi (UPEJ Unnes Physics Education Journal, 2021)
Teaching material is a learning resource that can help teachers to teach students in the classroom. Teaching materials used in several schools still use black and white images. The magazine has a variety of text views along with images combined with attractive colors. The materials contained in the teaching material also still emphasizes the description of the material rather than the application and has not linked the Islamic values listed in KI-1 in the 2013 curriculum. I-SETS-based learning approach (Islamic, Science, Environment, Technology, Society) is a contextual approach that links elements of Islam, science, environment, technology, and society. Magazine-based physics teaching material also contain a charge of character values proclaimed by the government. The purpose of this research are to compile a magazine-based physics teaching material, to determine the feasibility, readability, and practicality, as well as character development. The method used in this research is Research and Development. The results showed that magazine-based physics teaching material were compiled using several characteristics, the results of the feasibility test in terms of aspects of content, presentation, language, and graphics of teaching material were very feasible to use. Readability test results show that the teaching material is easy to read. The practicality test results show that teaching material were practical used by students. The development of religious character, discipline, responsibility, and communicative increased after using magazine-based physics teaching material.